POSITIONING SOCIAL DEVELOPMENT AS THE MAINSTREAM OF GOVERNMENT IMPLEMENTATION IN INDONESIA - Dyah Asri Gita Pratiwi; Didit Susiyanto (Politeknik Kesejahteraan Sosial Bandung, 2019)
The environment of governance and development that tends to change rapidly, is full of uncertainty and is full of the complexity of these problems, so a development policy and strategic programs are needed that are capable of responding carefully to problems and developing challenges. Government and society. The government must think strategically and visionary, to understand what is thought into effective strategic policies and programs to deal with changes in the surrounding environment, and develop a framework for implementing these strategies in a rational and